2015
DOI: 10.1002/pd.4635
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal whole‐exome sequencing: parental attitudes

Abstract: The majority of respondents felt prenatal whole-exome sequencing should be offered. Moreover, the majority wanted to know prenatally about treatable and non-treatable childhood and adult conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 26 publications
7
65
0
Order By: Relevance
“…Only 2.2% were opposed to the testing. However, over 70% reported an increased risk of adult onset conditions or a VUS would cause them anxiety …”
Section: Discussionmentioning
confidence: 99%
“…Only 2.2% were opposed to the testing. However, over 70% reported an increased risk of adult onset conditions or a VUS would cause them anxiety …”
Section: Discussionmentioning
confidence: 99%
“…showed that about 55% of parents undergoing prenatal CMA testing wanted to be informed of adult‐onset conditions found incidentally. Kalynchuk et al . and Walser et al .…”
Section: Discussionmentioning
confidence: 99%
“…showed that pregnant women and those undergoing prenatal CMA found it important to know about adult‐onset conditions, both treatable and non‐treatable. Nevertheless, the majority of the participants in Kalynchuk et al 's study believed that the identification of an increased risk for adult‐onset and/or a VOUS would cause them anxiety …”
Section: Discussionmentioning
confidence: 99%
“…Interviews were digitally recorded and transcribed. National Research Ethics Service approval to undertake this study was granted by West Midlands South Birmingham Committee (REC reference /WM/0150).…”
Section: Methodsmentioning
confidence: 99%